Patellofemoral Pain (I): Clinical Practice Guidelines Linked to the International Classification of Functioning, Disability and Health - Academy of Orthopaedic Physical Therapy of the American Physical Therapy Association (康复学报)
Academy of Orthopaedic Physical Therapy of the American Physical Therapy Association (APTA) created clinical practice guidelines on patellofemoral pain (PFP) based on the International Classification of Functioning, Disability and Health(ICF). Firstly, the guidelines described the formulation method, international classification of diseases (ICD) -10 codes and ICF codes corresponding to PFP. In addition, the guidelines reviewed the latest peer-review literature to grade different levels of evidence, and provided recommendations on assessment and physical therapy for patellofemoral pain with recommendation grades, which were divided into three parts: ①Impairment/function-based diagnosis: prevalence and incidence, pathoanatomical features, risk factors, diagnosis and classifications (overuse/overload without other impairment, muscle performance deficits, movement coordination deficits, and/or mobility impairments) and differential diagnosis.②Examination: outcome measures, activity limitations, physical impairment. The information about reliability and diagnostic accuracy with test methods was elucidated correspondingly. Moreover, the best-practice point was summarized.③Intervention: exercise therapy, taping, bracing, physical agents, needling therapies, patient education, combined interventions, etc. In each part, the detailed information of the cited literature data, summary, evidence synthesis and clinical rationales, gaps in knowledge as well as recommendations were introduced. The guidelines provided clinicians, including physiatrists and therapists, the overall rehabilitation protocol on management of PFP, also help them link up their work between each other based on the unified standard and consensus. The gaps in knowledge enlighten future research. The guidelines fully embody its role of guidance and standardability for clinical practice.